Metabolic effects of 1-week binge drinking and fast food intake during Roskilde Festival in young healthy male adults. Issue 1 (21st May 2021) - Demant, Mia; Suppli, Malte P; Foghsgaard, Signe; Gether, Lise; Grøndahl, Magnus F G; Dalsgaard, Niels B; Bergmann, Sigrid S; Lanng, Amalie R; Gasbjerg, Lærke S; Thomasen, Martin; Bagger, Jonatan I; Strandberg, Charlotte; et al.
Abstract : Aims/hypothesis: Metabolic effects of intermittent unhealthy lifestyle in young adults are poorly studied. We investigated the gluco-metabolic and hepatic effects of participation in Roskilde Festival (1 week of binge drinking and junk food consumption) in young, healthy males. Methods: Fourteen festival participants (FP) were studied before, during and after 1 week's participation in Roskilde Festival. Fourteen matched controls (CTRL) who did not participate in Roskilde Festival or change their lifestyle in other ways were investigated along a similar timeline. Results: The FP group consumed more alcohol compared to their standard living conditions (2.0 ± 3.9 vs 16.3 ± 8.3 units/day, P  < 0.001). CTRLs did not change their alcohol consumption. AUC for glucose during OGTT did not change in either group. C-peptide responses increased in the FP group (206 ± 24 vs 236 ± 17 min × nmol/L, P  = 0.052) and the Matsuda index of insulin sensitivity decreased (6.2 ± 2.4 vs 4.7 ± 1.4, P   = 0.054). AUC for glucagon during oral glucose tolerance test (OGTT) increased in the FP group (1037 ± 90 vs 1562 ± 195 min × pmol/L, P  = 0.003) together with fasting fibroblast growth factor 21 (FGF21) (62 ± 30 vs 132 ± 72 pmol/L, P  < 0.001), growth differentiation factor 15 (GDF5) (276 ± 78 vs 330 ± 83 pg/mL, P  = 0.009) and aspartate aminotransferase (AST) levels (37.6 ± 6.8 vs 42.4 ± 11 U/L, P  = 0.043). Four participants (29%) developed ultrasound-detectable steatosis and a mean strain elastography-assessed liver stiffness increased ( P  = 0.026) in the FP group. Conclusions/Interpretation: Participation in Roskilde Festival did not affect oral glucose tolerance but was associated with a reduction in insulin sensitivity, increases in glucagon, FGF21, GDF15 and AST and lead to increased liver stiffness and, in 29% of the participants, ultrasound-detectable hepatic steatosis.